2021
DOI: 10.1017/s1041610221002659
|View full text |Cite
|
Sign up to set email alerts
|

Assessing suicide ideation among older adults: a systematic review of screening and measurement tools

Abstract: Objectives: Rates of suicide in older adults may be higher than reported due to poor understandings of presentation of suicide ideation in this group. The objectives of this paper were to (i) review current measurement tools designed for older adults to detect suicide ideation and (ii) assess their psychometric properties. Design: We used a systematic review approach to identify measurement tools developed specifically for older adults without cognitive decline or impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Such statements highlight the further need for compassion and high-quality care that pays attention to the nuancing or tailoring of mainstream suicide prevention and mental health therapies for people in later life (Hafford-Letchfield et al, 2022a , b ). Validated screening tools used in suicidality with older people tend not to address these wider issues (Gleeson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such statements highlight the further need for compassion and high-quality care that pays attention to the nuancing or tailoring of mainstream suicide prevention and mental health therapies for people in later life (Hafford-Letchfield et al, 2022a , b ). Validated screening tools used in suicidality with older people tend not to address these wider issues (Gleeson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the aforementioned “gray area” behaviors presented by older people may lead to missed opportunities for healthcare providers to talk to these individuals about their suicide ideation and behavior (Shah and Erlangsen, 2014 ), particularly if the person has not received a diagnosis of depression. Gleeson et al's ( 2022 ) review of screening measures found that none of them actively included older people themselves in their development beyond item development (e.g., Edelstein et al, 2009 ; Carmel, 2017 ). Whilst the measures frequently included questions on social connectedness and support, none fully engaged with the theoretical issue of burdensomeness as a factor in determining suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of current measurement tools designed for older adults to assess suicide ideation (Gleeson et al, 2021) found wide variations. The authors highlighted the lack of consideration across gender, culture and minority status, and for the views of professionals and older people themselves to be considered.…”
Section: Wider Influential Factorsmentioning
confidence: 99%